Peritectic phase transition of benzene and acetonitrile into a cocrystal relevant to Titan, Saturn's moon. Issue 88 (25th September 2020) - McConville, Christina A.; Tao, Yunwen; Evans, Hayden A.; Trump, Benjamin A.; Lefton, Jonathan B.; Xu, Wenqian; Yakovenko, Andrey A.; Kraka, Elfi; Brown, Craig M.; Runčevski, Tomče
Abstract : Here we report the phase diagram of acetonitrile and benzene with the focus on a 1 : 3 acetonitrile : benzene cocrystal relevant to mineralogy of Titan, Saturn's moon. Abstract : Benzene and acetonitrile are two of the most commonly used solvents found in almost every chemical laboratory. Titan is one other place in the solar system that has large amounts of these compounds. On Titan, organic molecules are produced in the atmosphere and carried to the surface where they can mineralize. Here, we report the phase diagram of mixtures of acetonitrile and benzene, and provide an account of the structure and composition of the phases. To mimic the environment on Titan more accurately, we tested the stability of the structure under liquid ethane. The results provide new insights into the structure and stability of potential extraterrestrial minerals. In light of Dragonfly, NASA's upcoming mission to Titan, revisiting the fundamental chemistry of the smallest molecules with modern methods and techniques can have significant contributions to this epochal mission and can open new research directions in chemistry.